Integrative taxonomy of the ornamental ‘peppermint’ shrimp public market and population genetics of Lysmata boggessi, the most heavily traded species worldwide - J. Antonio Baeza; Donald C. Behringer (PeerJ, 2017)
The ornamental trade is a worldwide industry worth >15 billion USD with a problem of rampant product misidentification. Minimizing misidentification is critical in the face of overexploitation of species in the trade. We surveyed the peppermint shrimp ornamental marketplace in the southeastern USA, the most intense market for peppermint shrimps worldwide, to characterize the composition of species in the trade, reveal the extent of misidentification, and describe the population genetics of the true target species. Shrimps were bought from aquarium shops in FL, GA, SC, and NC. We demonstrated, contrary to popular belief (information from dealers), that the most heavily traded species in the market was Lysmata boggessi, an endemic species to the eastern Gulf of Mexico, and not Lysmata wurdemanni. Importantly, only when color pattern or genetic markers in conjunction with morphological traits were employed, was it was possible to unequivocally identify L. boggessi as the only species in the trade. The intensity of the market for peppermint shrimps in the USA has led to L. boggessi being the most traded species worldwide. Misidentification in the shrimp aquarium trade is accidental and involuntary, and is explained by remarkable similarity among congeneric species. Using sequences of the 16S-mt-DNA marker, we found no indication of population genetic structure in the endemic L. boggessi across  550 km of linear coast. Therefore, this species can be considered genetically homogeneous and a single fished stock. Still, we argue in favor of additional studies using more powerful markers (e.g., SNPs) capable of revealing genetic structure at a finer spatial-scale. Our results will help advance management and conservation policies in this lucrative yet understudied fishery. Future studies of other ornamental fisheries will benefit from using an integrative taxonomic approach, as we demonstrate here.